Parent perceptions of literacy learning of their young children on the autism spectrum in their first year of schooling. Issue 2 (August 2019) - O'Leary, Kathryn A; Flückiger, Bev; Paynter, Jessica; Westerveld, Marleen F
Many children on the autism spectrum struggle in their reading development. This study investigated parents' views of challenges and facilitators to literacy learning at home and at school in children on the autism spectrum who were in their first year of schooling. Thematic analysis of semi-structured interviews with 37 parents revealed parents' in-depth knowledge of their child's strengths and interests, which they utilised to engage their child in literacy learning activities at home. Parents raised concerns about the support their children were receiving at school, with many describing challenges with teacher understanding of autism spectrum disorders, limited adaptation of the curriculum to suit the child's learning needs and poor communication between school and home. The study challenges schools and educators to review and refine current practices to ensure individualised, learner-focused and inclusive pedagogies and practices to better support children on the autism spectrum.